A CONSTITUTIONAL PERSPECTIVE ON THE CONTENCIOUS TOPIC OF THE COMPENSATION FOR IMMOVABLE ASSETS ABUSIVELY TAKEN OVER BY THE ROMANIAN STATE DURING THE COMMUNIST REGIME - Valentina BĂRBĂȚEANU; Andrei MURARU (Challenges of the Knowledge Society, 2025)
Through the very Constitution adopted after the fall of the communist regime, the Romanian state, which became, thanks to the Revolution of 1989, a democratic state, governed by the rule of law, assumed the generic obligation to guarantee and protect the right to property. Under the wide dome of this purpose came also the reparation of injustices committed during the totalitarian regime, when numerous immovable assets (buildings and/or lands) were abusively removed from the private property of natural and legal persons and transferred to the property of the state. Starting from the 90s, the Romanian legislator developed a series of normative acts aimed at allowing former owners to regain possession of lost assets or obtain equivalent compensation in their place, when restitution in kind was no longer possible. Although very seductive and promising, this restorative legislation has not always fully achieved its goal. This paper intends to present the evolution of the regulations regarding the way of evaluating the compensation due to former owners or their heirs, analyzing it also through the lens of the ECtHR case-law and the CCR case-law. These two jurisdictions have made an important contribution in terms of rising awareness on the necessity of a fair determination of compensation. Their decisions influenced the Romanian legislator and made it modify several times the system of calculation and evaluation of the compensations. Apparently at this moment it has been reached a system that seems to have fewer shortcomings than the most previous ones, managing to a reasonable extent to offer fair satisfaction to former owners dispossessed during the communist regime.